Understanding the Justice in Agatha Christie’s Murder on The Orient Express - Lucky Aditya (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis deals with the understanding of justice in the novel. I use theory of retributive justice and two supporting theories about morality and code of conducts of private investigators. In this analysis, I analyze two characters who have strong reasons in helping me understand the justice. I analyze Hercule Poirot because he is the main character and also symbolizes justice due to his moral choice in the story. Next, I analyze Linda Arden because she is the mastermind and has the strong emotional scar to bring out her point of view of justice. The conclusion that can be found in this analysis is that justice in retribution includes an action that precedes the legal procedure. It can justify some action outside the legal written law. Key words: Justice, morality, code, legality, procedure, criminal